2018
DOI: 10.1016/j.aucc.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical audits to improve critical care: Part 1 Prepare and collect data

Abstract: Clinical audits are used to examine current practice, compare this with established best practice and implementing change, to ensure patients receive the most effective treatment. They are successful in improving the quality and safety of care provided, and thereby clinical outcomes. Clinical audits are ubiquitous throughout critical care practice, but without the necessary focus, engagement, preparation, method, evaluation and communication, they may be a waste of resources. This article is the first of a two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…35 Clinical audits, when incorporated with feedback and clear action plans for improvement, can lead to modest but important improvements in professional practice, 36,37 potentially improving the quality and safety of care, and consequently, clinical outcomes. 38,39 The only demographic or clinical characteristic associated with interpreter service utilisation in this study was sex, with females more likely to receive an interpreter when required than males. Blay et al also found female patients were more likely to receive an interpreter.…”
Section: Discussionmentioning
confidence: 83%
“…35 Clinical audits, when incorporated with feedback and clear action plans for improvement, can lead to modest but important improvements in professional practice, 36,37 potentially improving the quality and safety of care, and consequently, clinical outcomes. 38,39 The only demographic or clinical characteristic associated with interpreter service utilisation in this study was sex, with females more likely to receive an interpreter when required than males. Blay et al also found female patients were more likely to receive an interpreter.…”
Section: Discussionmentioning
confidence: 83%
“…The results of this comparison are then sent to the individual or the group as a feedback. 3,30,31 Even if there have been different attempts to standardize A&F management and processing, [32][33][34] there is still a lot of heterogeneity in literature concerning the correct methodology to collect and analyze data and for the choice of right indicators. The Italian Friuli Venezia Giulia region (FVG) takes part to a national project to evaluate the A&F approach applied to different clinical areas.…”
Section: Discussionmentioning
confidence: 99%
“…Chambers, Wakley opined that clinical audit involves a cycle of systematic activities starting from problem identification and standard definition, through observation and data recording, comparison of audit results with the standard, implementation of proposed changes, as well as evaluation of the resultant effects of the changes. According to Ullman, Ray‐Barruel, Rickard, Cooke, the introduction of clinical audit in hospitals was found to be associated with a multiplicity of favorable outcomes such as lower rates of needless cesarean section deliveries, higher levels of overall prescription accurateness of antibiotics by general dental practitioners, reduced delays in patient discharge and lower readmission rates, increased professional knowledge and enhanced teamwork, and communication among nursing staff as well as more fast evaluation of unstable health conditions and lower ratios of patient mortality.…”
Section: Literature Reviewmentioning
confidence: 99%